1982
DOI: 10.21273/hortsci.17.5.760
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability for Fruit Set, Flower Drop, and Underdeveloped Ovaries in Some Heat-tolerant Tomatoes1

Abstract: Seven tomato genotypes (Lycopersicon esculentum Mill) were crossed in all except reciprocal combinations in a diallel test for heat tolerance. S6916 had the highest general combining ability (GCA) value for heat tolerance, indicating that it transmitted good fruit setting abilty at high temperatures to its progeny. BL6807 had the second highest GCA value for fruit set but also transmitted underdeveloped ovaries. L401 had the lowest GCA value for fruit set. Additive gene action was more important than nonadditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Tuber plug sections were ashed in glass vials for 12 hr at 500°. The ash was suspended in 3 ml of 1 n HC1, and 15 ml of scintillation fluid was added and counted on an IsoCap/300 liquid scin tillation counter (5). Initially, the infiltrated 45Ca was distrib uted as follows: 45% stem end, 20% bud end, and 35% middle section.…”
Section: Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…Tuber plug sections were ashed in glass vials for 12 hr at 500°. The ash was suspended in 3 ml of 1 n HC1, and 15 ml of scintillation fluid was added and counted on an IsoCap/300 liquid scin tillation counter (5). Initially, the infiltrated 45Ca was distrib uted as follows: 45% stem end, 20% bud end, and 35% middle section.…”
Section: Daysmentioning
confidence: 99%
“…Our conclusion is that none of the above characters could be singled out as solely re sponsible for poor tomato fruit set at high summer temperatures. Hanna et al (5) re ported on the genetic effects of heat tolerance and found that additive gene action played a significant part and was more important than nonadditive effects.…”
Section: Louisiana State Univesity Baton Rouge La 70803mentioning
confidence: 99%